The Global Convergence of a New Mixed Conjugate Gradient Method for Unconstrained Optimization - Yang Yueting; Cao Mingyuan (Journal of Applied Mathematics)
We propose and generalize a new nonlinear conjugate gradient method for unconstrained optimization. The global convergence is proved with the Wolfe line search. Numerical experiments are reported which support the theoretical analyses and show the presented methods outperforming CGDESCENT method.